2021
DOI: 10.1007/s11548-021-02417-x
|View full text |Cite
|
Sign up to set email alerts
|

Capsule networks for segmentation of small intravascular ultrasound image datasets

Abstract: Purpose Intravascular ultrasound (IVUS) imaging is crucial for planning and performing percutaneous coronary interventions. Automatic segmentation of lumen and vessel wall in IVUS images can thus help streamlining the clinical workflow. State-of-the-art results in image segmentation are achieved with data-driven methods like convolutional neural networks (CNNs). These need large amounts of training data to perform sufficiently well but medical image datasets are often rather small. A possibility … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The PDN-AC is superior to state-of-the-art IVUS segmentation networks IVUS-Net (Yang et al 2018), DPU-Net (Yang et al 2019), MFAU-Net (Xia et al 2020), (Nishi et al 2021) and (Bargsten et al 2021), according to table 4 and figure 10. These networks exploit individual 2D frames, ignoring longitudinal relations in IVUS sequences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The PDN-AC is superior to state-of-the-art IVUS segmentation networks IVUS-Net (Yang et al 2018), DPU-Net (Yang et al 2019), MFAU-Net (Xia et al 2020), (Nishi et al 2021) and (Bargsten et al 2021), according to table 4 and figure 10. These networks exploit individual 2D frames, ignoring longitudinal relations in IVUS sequences.…”
Section: Discussionmentioning
confidence: 96%
“…Modified from the IVUS-Net, a dual path U-Net (DPU-Net) with specific IVUS image augmentation was proposed to learn from a small training set (Yang et al 2019). (Xia et al 2020), (Nishi et al 2021), and (Bargsten et al 2021) introduced powerful U-Net, DeepLabV3, and CapsNet into IVUS segmentation with slight architecture modifications, respectively. A model cascading three modified U-Nets was presented by Li et al (2021).…”
Section: Related Workmentioning
confidence: 99%
“…The number of studies that fell under the intersection of (RBA, RBM, RBS), (RBA, RBS), and (RBM, RBS) was two, three, and one, respectively, whereas no common studies were found under intersection of (RBA, RBM). On the other hand, the number of studies under moderate bias (out of 60 studies) for RBM, RBA, and RBS was 9 (15%) [43,69,74,78,80,83,95,96,98], 20 (33%) [43,49,57,61,64,69,73,74,78,80,82,83,[86][87][88]95,98,120,160,161], and 18 (30%) [44][45][46][47][50][51][52][53][54][55][59][60][61]71,72,75,76,96], respectively. The number of studies that fell under the intersection of (RBA, RBS), (RB, MRBS), and (RBA,...…”
Section: Comparative Study Of Three Bias Strategies Based On Venn Dia...mentioning
confidence: 99%
“…Bargsten et al [11] scientifically examined distinct capsule network framework variants and enhanced the accuracy of the segmentation of IVUS images. Later, the capsule network is compared to convolutional neural network (CNN) under different quantities of network parameters and training images.…”
Section: Related Workmentioning
confidence: 99%